Ukrainian Folk Music and its Role in the Education of the Individual: from the History of the Issue - Yakivchuk, Galyna (Pedagogical Discourse, 2013)
The article deals with the essence of the concepts of «folk art» focuses on its components − «musical folklore». The different times phased approaches of spiritual sphere peculiarities formation of the Ukrainian folk music and its connection to historical phenomena and events are traced. It is stressed on the importance and primacy of learning, understanding of folklore as a set of material and spiritual culture, the worldview and value system of education formation based on spiritual and moral foundations. The basic approaches of scientists, folklorists, musicians, teachers on the use of Ukrainian folk music and its value in educating future teachers of creative personality are defined.